Edukasi Penerapan Standar Oprasional Prosedur oleh Petugas dalam Rangka Pencegahan Penyakit Potensial Wabah di Pintu Masuk Pelabuhan Malundung Kota Tarakan - Agustin Agustin; Sri Wahyu Ekowati (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Ports serve as strategic entry points with a high potential for the transmission of infectious diseases and outbreaks, thus requiring the effective implementation of Standard Operating Procedures (SOPs) by port health officers. This community service activity aims to provide SOP education for officers to prevent potential outbreaks at ports, based on the latest literature review. The method used involves delivering educational sessions supplemented by discussions drawn from various academic sources, government regulations, and technical guidelines relevant to the 2011–2024 publication period. These include Minister of Health Regulation No. 2348/2011, Ministerial Decrees from 2015–2023, and scientific publications related to outbreak prevention at ports. The results indicate that comprehensive SOP education encompasses seven key components: understanding the strategic role of ports in border control, mastery of the officers’ multidimensional tasks, outbreak surveillance and control components, effective health information communication methods, the central role of health personnel as educators, integration with the national health system, and continuous evaluation of the educational program. The discussion highlights that the success of SOP implementation is highly dependent on the quality of education provided to the officers, with an emphasis on ongoing training, emergency simulations, and cross-sector coordination. Optimal SOP education will enhance officers’ preparedness to detect, prevent, and control potential outbreaks, enabling ports to function as effective barriers in protecting public health from infectious disease threats, in line with Indonesia’s commitment to the International Health Regulations (IHR) 2005.